2003
DOI: 10.1074/jbc.m210476200
|View full text |Cite
|
Sign up to set email alerts
|

A Soluble Form of the First Extracellular Domain of Mouse Type 2β Corticotropin-releasing Factor Receptor Reveals Differential Ligand Specificity

Abstract: The heptahelical receptors for corticotropin-releasing factor (CRF), CRFR1 and CRFR2, display different specificities for CRF family ligands: CRF and urocortin I bind to CRFR1 with high affinity, whereas urocortin II and III bind to this receptor with very low affinities. In contrast, all the urocortins bind with high affinities, and CRF binds with lower affinity to CRFR2. The first extracellular domain (ECD1) of CRFR1 is important for ligand recognition. Here, we characterize a bacterially expressed soluble p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
74
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 55 publications
(86 citation statements)
references
References 46 publications
8
74
0
Order By: Relevance
“…Many studies have shown that the ECD1s of the CRF receptors constitute major ligand-binding sites. Chimeric receptors expressing the ECD1s bind CRF family ligands with high affinity, as do soluble proteins corresponding to the ECD1s (2)(3)(4)(5)(6)(7)(8)(9). Studies of other B1 receptors report similar data (10 -16).…”
supporting
confidence: 66%
“…Many studies have shown that the ECD1s of the CRF receptors constitute major ligand-binding sites. Chimeric receptors expressing the ECD1s bind CRF family ligands with high affinity, as do soluble proteins corresponding to the ECD1s (2)(3)(4)(5)(6)(7)(8)(9). Studies of other B1 receptors report similar data (10 -16).…”
supporting
confidence: 66%
“…1A and SI Table 1). The 3D structure of ECD1-CRF-R2␤ at pH 5 is an SCR motif similar to the fold at pH 7.4 (18) with three disulfide bonds (Cys-45-Cys-70, Cys-60-Cys-103, and Cys-84-Cys-118) (20), and two antiparallel ␤-sheet regions from residues 63-64 (␤1-strand), 70-71 (␤2-strand), 79-82 (␤3-strand), and 99-102 (␤4-strand) (18) (Fig. 1 A).…”
Section: Resultsmentioning
confidence: 99%
“…However, the binding domain is also crucial for signaling because it controls the binding affinity of the ligand and determines the orientation of the ligand for receptor signaling. Some determinants of binding specificity and affinity are possibly also located in the signaling domains, as suggested by the observation that Ucn 3 and sauvagine bind to CRF-R2␤ with high affinity, but not to the ECD1 of CRF-R2␤ (SI Table 3) (20). It is noteworthy to mention that membrane-peptide interactions seem to be less important in receptor binding (see SI Text).…”
Section: Crf Ligand-receptor Interactions Have a Common Binding Modementioning
confidence: 91%
See 1 more Smart Citation
“…Two subtypes of CRF receptors have been characterized that exhibit differential affinity for the ligands [6,7]. We have recently identified the first extracellular domain of the CRF type I receptor as playing a major role in agonist and antagonist binding [8,9]. In particular the synthetic peptide antagonist Astressin binds the first extracellular portion with high affinity.…”
mentioning
confidence: 99%